PENGARUH JENIS PISANG (Musa paradisiaca) TERHADAP KARAKTERISTIK TAPAI PISANG DI BANYUWANGI : The Influence Of Banana Type (Musa paradisiaca) On The Characteristics Of Banana Tapai In Banyuwangi - Helmy Ahfas; Bagus Setyawan; Arfiati Ulfa Utami (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2024)
The general aim of this research is to determine the effect of banana type on the organoleptic properties of tapai. The specific aim of this research is to determine the differences in the nutritional content of tapai from several types of bananas and to find out which types of bananas are suitable for banana tapai. This research was carried out from May to August 2017. This experiment used RAL which consisted of 4 types of bananas including kepok bananas, crew bananas, wood bananas and raja/sajen bananas. The results of the research show that from the organoleptic test the most preferred by slot thailand the panelists is kepok banana and from the chemical test it shows that wood banana has the highest protein content than other types of banana, namely 1.21% and raja/sajen banana has the highest sugar content than other types of banana. the other banana is 12.38%.